2009
DOI: 10.5551/jat.2642
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of an ELISA Kit for Platelet-Derived Microparticles by Joint Research at Many Institutes in Japan

Abstract: Aim: Platelet-derived microparticles (PDMPs) play roles in normal hemostatic responses to vascular injury because they possess prothrombinase activity. Although the most widely used method for studying PDMP is flow cytometry, we previously developed an enzyme-linked immunosorbent assay (ELISA) method as an easier and more reproducible PDMP assay. The purpose of this study was to use various clinical settings to verify whether this ELISA method can produce equivalent results to flow cytometry for PDMP. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 47 publications
0
36
0
Order By: Relevance
“…PDMPs can modulate coagulation through both direct and indirect mechanisms. Therefore, MP concentration increases are documented in almost all thrombotic diseases occurring in venous or arterial beds 3,4) . Furthermore, elevated MP levels are found in conditions associated with inflammation, cellular activation, angiogenesis, and vascular dysfunction 1, 2) .…”
Section: See Article Vol 22: 773-782mentioning
confidence: 99%
“…PDMPs can modulate coagulation through both direct and indirect mechanisms. Therefore, MP concentration increases are documented in almost all thrombotic diseases occurring in venous or arterial beds 3,4) . Furthermore, elevated MP levels are found in conditions associated with inflammation, cellular activation, angiogenesis, and vascular dysfunction 1, 2) .…”
Section: See Article Vol 22: 773-782mentioning
confidence: 99%
“…Microparticle activity of blood plasma denotes the fragmentation of platelets and the release of cell membrane vesicles. Microparticles impose thrombotic burden on circulating blood [67] and were recently found to correlate with atherosclerosis and a risk for major adverse cardiovascular events, such as heart infarction or stroke [68,69]. In analysing the results, it is also important to note that the values of the free haemoglobin levels were within the range of the specified standards developed for the preparation and storage of whole blood.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that ELISA assays correlate well with FACS determinations, although they require particles that simultaneously express 2 platelet markers 9,10 . Since PDMP display heterogeneity in terms of size and marker expression, an ELISA, like any other detection method, may miss particle subpopulations.…”
Section: Rheumatologymentioning
confidence: 99%